Word Frequency Is Associated With Cognitive Effort During Verbal Working Memory: A Functional Near Infrared Spectroscopy (fNIRS) Study - Berglund-Barraza, Amy; Tian, Fenghua; Basak, Chandramalika; Evans, Julia L. (Frontiers in Human Neuroscience, 2019)
Purpose: Psycholinguistic models traditionally view verbal working memory capacity as independent from linguistic features; connectionist models suggest otherwise. Moreover, lexical processing studies show high frequency words differ in cognitive effort from low frequency words, although these effects during concurrent processing of words in working memory are unknown. This novel study examines potential differences in cognitive effort, as measured by differences in HbO2 and Hb, for high frequency versus low frequency words during a working memory paradigm. Methods: A total of 21 neurologically typical participants (age 18-23) completed an auditory, n-back, working memory task comparing performance with high- as compared to low- frequency words. Hemodynamic changes in the prefrontal cortex were recorded with a continuous-wave functional near-infrared spectroscopy (fNIRS) device. Behavioral data (accuracy, reaction time) were recorded using E-prime. Results: Differences in word frequency were evident at both behavioral and neurological levels. Participants were more accurate, albeit slower in identifying the target two back in a sequence for high- as compared to low-frequency words. Patterns of hemodynamic changes were also significantly different between HF and LF conditions. Conclusion: The results from this study indicate that the behavioral and neurological signatures inherent in holding high- versus low-frequency words in working memory differs significantly. Specifically, the findings from this study indicated that words differing in frequency place different demands on cognitive processing load in memory updating tasks.